Treatment and outcomes of nasopharyngeal carcinoma in a unique non-endemic population. (March 2021) - Howlett, Joel; Hamilton, Sarah; Ye, Annette; Jewett, David; Riou-Green, Breanna; Prisman, Eitan; Thamboo, Andrew
Highlights: The largest study evaluating treatment and outcomes of nasopharyngeal carcinoma in a non-endemic population. Histologic subtype and primary treatment type did not affect overall survival. Non-keratinizing histology and radiotherapy had a propensity for disease recurrence. Patients experienced more locoregional and less distant recurrence compared to endemic regions. This recurrence cohort may be more amenable to curative salvage therapy. Abstract: Objective: Nasopharyngeal carcinoma (NPC) is common in Southeast Asia. Due to the influx of immigrants from this region, the incidence in British Columbia is increasing. Current literature from non-endemic populations encompasses heterogeneous cohorts. This study examines NPC in a North American population, with a high incidence, to understand the population's characteristics, treatment outcomes and recurrence patterns. Methods and materials: A retrospective analysis of patients treated for primary and recurrent NPC over 15-years. Regression analyses were used to identify predictors of disease recurrence and death. A subgroup analysis of the locoregional recurrence cohort was conducted. Five-year survival outcomes were determined. Results: 601 patients were included. Asian ethnicity comprised 77% and the majority had non-keratinizing carcinoma (81%). In total, 19.3% of patients experienced recurrence: 58% local, 22% regional and 20% distant. Five-year overall survival was 70%. Smoking, advancing T-stage, poorer performance status and advanced overall stage were all associated with worse overall survival (p < 0.05). Asian ethnicity improved overall survival but not recurrence free survival. Similar features in addition to non-keratinizing histology were associated with increased locoregional recurrence (p < 0.05). Competing risk analysis indicated radiotherapy alone had a higher recurrence relative to chemoradiotherapy (HR 1.91, CI 1.17–3.09, p = 0.01). Conclusions: We report the largest study evaluating treatment and outcomes of NPC in a non-endemic population. This unique population falls between described endemic and non-endemic populations. Non-keratinizing pathology and primary radiotherapy did not affect survival; however, both had a propensity for recurrence. Finally, patients experienced more locoregional and less distant recurrence, supporting that this cohort may be amenable to curative salvage therapy.